Step by Step: Finding Compensatory Order in Science. (June 2013) - Rutjens, Bastiaan T.; van Harreveld, Frenk; van der Pligt, Joop
People are motivated to maintain the belief that they live in an orderly world in which things are under control. Previous research has shown that perceptions of order can be maintained via two routes: affirming personal control over one's life and future outcomes, and bolstering one's belief in external systems or agents that exert control over the world. Both religion and sociopolitical institutions can provide subjective and socially sanctioned security in the context of low personal control or disorder in one's environment. In this article, we argue that belief in science and progress could serve a similar function. Science is not only assumed to simplify people's lives; it also creates a sense of order and predictability. We show that perceiving order (regardless of external agency) can be sufficient to combat lack of control, and that perceptions of order can be derived from science and from more general beliefs about progress. We also discuss findings from our research addressing the processes underlying these effects and the functionality of compensatory beliefs and perceptions. We conclude that endorsing scientific theories and beliefs in societal and scientific progress helps people regulate threats to order and control, as long as these theories and beliefs suggest that the world is (or will be) an orderly place.